Empowering Women-Led MSMEs: The Role of Sharia Financial Literacy and Management - Nova Rini; Supriatiningsih Supriatiningsih; Nanda Devira Fitriyanthi (Research of Islamic Economics, 2026)
The growth of Islamic finance in Indonesia has increased the importance of Sharia financial literacy for MSMEs. However, women-owned MSMEs participating in the Aisyiyah Entrepreneur School (SWA) in Jakarta had not previously received structured training in Sharia financial literacy and financial management, limiting their ability to access Sharia-compliant financial services and improve business performance. This community service program aimed to enhance participants’ Sharia financial literacy and financial management skills through a training program. The program involved 21 women MSME owners from the Aisyiyah organization in Jakarta and employed a pre-test and post-test design to evaluate learning outcomes. The results showed that the average participants’ score increased from 32,21 to 35,11, representing an improvement of 9% in their understanding of Sharia financial literacy and financial management. Participants also demonstrated a strong intention to apply Sharia financial instruments and adopt more professional financial management practices in their businesses. The study was limited by the relatively small number of participants representing the five municipalities of DKI Jakarta. Nevertheless, the findings demonstrate that structured training is an effective approach to strengthening Sharia financial literacy and financial management among women-owned MSMEs and can serve as a practical model for similar community empowerment programs.